Risk assessment of online child abuse material (CAM) offenders: a review of existing tools. Issue 2 (12th December 2017) - Garrington, Catherine; Chamberlain, Peter; Rickwood, Debra; Boer, Douglas P.
Abstract : Purpose: The purpose of this paper is to summarise the available risk and assessment tools for child abuse material (CAM) offenders. Noting the rise of internet-based offences surrounding CAM, it has been proposed that there may be substantial differences between internet only (IO) offenders, contact only and mixed profile sexual offenders. Design/methodology/approach: Through online searches, risk assessment tools for sexual offenders were identified. Scoring manuals were consulted for applicability to IO offenders. Findings: Nine risk assessment tools for sexual offenders were included. Risk assessment tools for sexual offenders use cautionary language regarding the application of sexual offence risk assessment tools to IO offenders. An additional five tools were identified specifically addressing IO offenders. Three of these tools address risk assessment and two assess cognitions and behaviours. Research limitations/implications: Limitations include the identification of static and dynamic risk factors and the application of structured professional judgement. Practical implications: By drawing together existing tools and recommendations for use with the IO offender population, a gap is identified for CAM specific risk assessment tools. Originality/value: Appropriate risk assessment, case planning and treatment will contribute to the appropriate management and treatment of the IO offender population.